PB1 mutations as key drivers of influenza A virus evolution - Fang, Canxin; Sun, Xin; Feng, Yutong; Song, Hong; Wang, Shengyu (Frontiers in Microbiology, 2026)
Influenza A virus (IAV) is a zoonotic pathogen with a broad host range, posing an ongoing threat to global public health. As the core subunit of the IAV polymerase, polymerase basic protein 1 (PB1) is essential for viral replication and transcription, and its mutations are key drivers of viral evolution. This review evaluates the impact of PB1 mutations on IAV evolution, with a focus on polymerase activity, host adaptation, transmissibility, and virulence. Additionally, it discusses the implications of these mutations for vaccine development. The review aims to provide insights that can inform influenza surveillance, identify novel antiviral targets, and guide vaccine design.